HASRAT WISRAN HADI DALAM PERSIDEN: KAJIAN PSIKOANALISIS LACANIAN (The Desire of Wisran Hadi in Persiden, a Lanian Psychoanalysis Study) - Manik, Ricky Aptifive (Salingka, 2015)
AbstractIn its history, desire is created from the lack of subjects. Writing a literary work is an effort of an author to cover their lack of subjects. The novel entitled Persiden is an effort of Wisran Hadi (WH) to cover his lack in Minangkabau social and cultural life. Various roles of social status of Minangkabau people which emerged in Persiden show a sort of anxiety which then becomes the manifestation of WH’s desire. This research aims to identify WH’s desire and how the desire formed in Persiden. The research of this WH’s desire will use Lacanian Psychoanalysis (PL). Through this PL, the method of metaphor and metonymy will be used to find the markers of WH’s desire. This study finds that Minangkabau people in their social and cultural life are constantly faced into paradoxical condition while they position themselves as an uncle, a son-in-law, a mother, a nephew/niece, and a son/daughter. It causes WH ends his identity as paradoxical Minangkabau person who has strong desire to the markers: ‘responsible’, ‘rich’, hard-working’, ‘leader’, ‘talented’, ‘obey’, ‘dicipline’, etc.Keywords: desire, metaphor, Minangkabau, paradox, Wisran HadiAbstrakDalam sejarahnya, hasrat terbentuk dari rasa kekurangan subjek. Menulis karya sastra merupakan upaya pengarang untuk menutupi kekurangan tersebut. Novel Persiden merupakan upaya Wisran Hadi (WH) dalam menutupi kekurangan dirinya di dalam kehidupan sosialkultural Minangkabau. Berbagai peran status sosial orang Minang yang dihadirkan dalam Persiden menunjukan adanya kegelisahan yang kemudian menjadi manifestasi hasrat WH. Tujuan penelitian ini adalah mengidentifikasi hasrat WH dan bagaimana hasrat itu terbentuk dalam Persiden. Telisik hasrat iniakan menggunakan kajian Psikoanalisis Lacanian (PL). Melalui PL ini akan digunakan metode metafora dan metonimia dalam mengidentifikasi dan terbentuknya hasrat WH. Kajian ini menemukan bahwa orang Minang dalam sosialulturalnya selalu pada kondisi yang paradoks, baik sebagai mamak,semenda, ibu, kemenakan dan anak. Inilah yang membuat WH menyudahi identitasnya selaku orang Minang yang paradoks dengan berhasrat pada penanda-penanda: ‘bertanggung jawab’, ‘kaya’, ‘pekerja keras’, ‘pemimpin’, ‘berkemampuan’, ‘taat’, ‘disiplin’ dst.Kata kunci: hasrat, metafora, Minangkabau, paradoks, Wisran Hadi